2007
DOI: 10.1038/sj.onc.1210682
|View full text |Cite
|
Sign up to set email alerts
|

p51/p63 inhibits ultraviolet B-induced apoptosis via Akt activation

Abstract: The epidermis must be protected against excess apoptotic cell death in response to ultraviolet-B (UV-B) irradiation. p53 is known to be critical for this protection. Although the p53 family member DNp51B/DNp63a (an N terminaldeleted form of p51/p63) is abundantly expressed in keratinocytes, its contribution to UV-B-dependent apoptosis is largely unknown. We found that, after a transient increase, DNp51B is downregulated in UV-B-irradiated keratinocytes undergoing apoptosis, whereas p53 is upregulated with dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…As shown in Figure 7a, UVB irradiation leads to a strong decrease of all FLIP variants; p63 levels are also decreased, in these conditions, as reported earlier. 27,28 As a control for this analysis, we verified the levels of Jun-B, whose expression levels are known to be increased, 29 and (Figure 7a). We overexpressed DNp63a in NHEK, exposed them 24 h after transfection to UVB irradiation, and analysed FLIP by semiquantitative RT-PCR and western blots: we observed increased FLIPr levels, but not of the other two splicing isoforms, FLIPs and FLIPl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 7a, UVB irradiation leads to a strong decrease of all FLIP variants; p63 levels are also decreased, in these conditions, as reported earlier. 27,28 As a control for this analysis, we verified the levels of Jun-B, whose expression levels are known to be increased, 29 and (Figure 7a). We overexpressed DNp63a in NHEK, exposed them 24 h after transfection to UVB irradiation, and analysed FLIP by semiquantitative RT-PCR and western blots: we observed increased FLIPr levels, but not of the other two splicing isoforms, FLIPs and FLIPl.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 We investigated whether p63 levels might impact on caspase-8 activation, functionally inactivating p63 in NHEK cells by shRNA: (Figure 3b, and data not shown). Reduction of p63 significantly increased caspase-8 activation, compared with the levels in control cells, as shown in confocal microscopy of irradiated keratinocytes with antibodies against cleaved caspase-8 (Figure 3a and c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past few years it has been suggested that DNp63 acts as an antiapoptotic factor in both cancer and development (Carroll et al, 2006;Cheng et al, 2006;Lee et al, 2006;Ogawa et al, 2008;Borrelli et al, 2009;Mundt et al, 2010). During mammalian development, apoptosis in the bladder epithelium is increased in the absence of DNp63; however, the restitution of DNp63 expression reverses the increased levels of apoptosis in the urothelium .…”
Section: Dnp63 Is An Anti-apoptotic Factor During Epidermal Developmentmentioning
confidence: 94%
“…7,8 The survival factor Akt can increase DNp63a levels and in turn, DNp63a protects against UV-B-induced apoptosis via Akt activation. 9,10 However, the mechanism behind the positive feedback loop between DNp63a and Akt has not been described. Akt activation can be negated by phosphatase and tensin homolog deleted on chromosome 10 (PTEN).…”
mentioning
confidence: 99%